2018
DOI: 10.3390/ijfs6020043
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Persistence of European Football Clubs under UEFA’s FFP

Abstract: The goal of this study was to examine the predictability and persistence of earnings of the European football clubs and whether the new Union of European Football Associations (UEFA) Financial Fair Play (FFP) licensing regulation has forced clubs to produce a more predictable earnings stream. We utilized a sample of 109 European top-tier clubs over the period 2008-2016, summing up to 844 firm-year observations. Empirical evidence indicated that the cash flow component of earnings is more relevant in predicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
14
0
2
Order By: Relevance
“…For example, earnings persistence in Korean companies during the period of 1995-2006 was lower compared to the developed countries . Dimitropoulos and Koronios (2018) indicated that current cash flows had more predictive ability of future earnings than current earnings for 109 European top-tier clubs during the period of 2008-2016. Senan (2019) found that current cash flows from operations had more predictive ability compared to current earnings for the Saudi companies during the period of 2006-2015, and he also found that accruals increased the predictive ability of current earnings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, earnings persistence in Korean companies during the period of 1995-2006 was lower compared to the developed countries . Dimitropoulos and Koronios (2018) indicated that current cash flows had more predictive ability of future earnings than current earnings for 109 European top-tier clubs during the period of 2008-2016. Senan (2019) found that current cash flows from operations had more predictive ability compared to current earnings for the Saudi companies during the period of 2006-2015, and he also found that accruals increased the predictive ability of current earnings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The financial principles of the FFP are not far from the common logic of financial sustainability, being: (a) the debt must be maintained at manageable levels and paid on time; and (b) expenses must be kept within the parameters of each club's ability to pay based on their income (Cordery, Sim & Baskerville, 2013). Dimitropoulos and Koronios (2018) complement previous authors by describing that UEFA has introduced sustainability as the most important financial feature of the new licensing regulation, as clubs need to prove that they will honor their debt obligations (without late payments).…”
Section: Installment Of Debts Of Football Clubsmentioning
confidence: 99%
“…Mais la plupart des travaux restent centrés sur le seul impact financier du FPF. Ainsi, un numéro spécial sur le financement du sport dans l'International Journal of Financial Studies s'est concentré sur l'impact du FPF sur une série d'éléments financiers tels que les flux de trésorerie et les bénéfices ainsi que les frais d'audit (Dimitropoulos et Koronios, 2018 ;Mareque et al, 2018). Franck (2018) a également proposé des explications plausibles au redressement financier observé dans le football européen de première division, tout en appelant à une évaluation de l'efficacité réelle du dispositif, après cinq années d'application de la règle de l'équilibre financier.…”
Section: Revue De Littératureunclassified